Graphene: Preparation, tailoring, and modification. Issue 1 (19th January 2023) - Li, Mingyao; Yin, Bing; Gao, Chunyan; Guo, Jie; Zhao, Cong; Jia, Chuancheng; Guo, Xuefeng
Abstract: Graphene is a 2D material with fruitful electrical properties, which can be efficiently prepared, tailored, and modified for a variety of applications, particularly in the field of optoelectronic devices thanks to its planar hexagonal lattice structure. To date, graphene has been prepared using a variety of bottom–up growth and top–down exfoliation techniques. To prepare high‐quality graphene with high yield, a variety of physical exfoliation methods, such as mechanical exfoliation, anode bonding exfoliation, and metal‐assisted exfoliation, have been developed. To adjust the properties of graphene, different tailoring processes have been emerged to precisely pattern graphene, such as gas etching and electron beam lithography. Due to the differences in reactivity and thermal stability of different regions, anisotropic tailoring of graphene can be achieved by using gases as the etchant. To meet practical requirements, further chemical functionalization at the edge and basal plane of graphene has been extensively utilized to modify its properties. The integration and application of graphene devices is facilitated by the combination of graphene preparation, tailoring, and modification. This review focuses on several important strategies for graphene preparation, tailoring, and modification that have recently been developed, providing a foundation for its potential applications. Abstract : Graphene is a key material for a new generation of electronic devices with unique electrical properties. In this review, current advances in the preparation, tailoring, and modification of graphene to obtain high‐quality graphene with precisely controlled patterning and specific functional groups are summarized.